Understanding care experiences amongst immigrant and refugee clients in a Ryan-White funded HIV clinic - Sirey Zhang; Peggy-ita Obeng-Nyarkoh; Antonia Altomare; Richard Zuckerman (Communications Medicine)
Abstract Background Immigrants and refugees with HIV in high-income countries face unique challenges navigating their diagnoses due to cultural, social, and structural barriers, which impact access and adherence to care. This project sought to improve care systems by gathering experiences from clients and care providers. Methods A focused ethnography was conducted using participant observation and standardized interviews with 18 clients and 4 clinic team members from three Dartmouth Health Ryan White-HIV clinics in New Hampshire, USA. Ten clients consented to recorded interviews, while 8 shared their stories informally. Interpretation services were provided as needed, and clients received compensation for participation. Data analysis involved associating codes with keywords to identify categories, from which themes were developed. Results Client informants encompass a spectrum of documentation statuses and lengths of residence. Clinic team member informants include physicians, nurses, and care coordinators. Findings emphasize the benefits in care experience when power dynamics are mitigated within clinical settings—both between clients and clinicians and among care team members. Client informants express fears of stigma and ostracization within immigrant communities, describe challenges with healthcare access related to immigration status, and voice a general desire for the clinic team to engage more in family and community communication and advocacy. Conclusions This ethnographic study highlights the importance of redefining culturally competent care by moving beyond narrow associations with ethnoracial identity toward a multidimensional approach. This approach considers interpersonal interactions, hybridized identities, diasporic experiences, and structural inequities. By reframing cultural competence and implementing actionable strategies to address structural vulnerabilities, clinicians transform each healthcare interaction into an opportunity to deliver equity-oriented care and enhance the well-being of immigrant and refugees with HIV.